2000
DOI: 10.1159/000053628
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD69 Expression on Eosinophil Precursors by Interferon-γ

Abstract: The purpose of this study was to determine whether interferon-γ (IFN-γ) induced CD69 expression by eosinophil precursors. Eosinophil precursors were induced from CD34+ cord blood cells using recombinant human interleukin-3 (IL-3) and interleukin-5 (IL-5). On day 14 of culture, cells constitutively expressed CD69 and the IFN-γ receptor (IFN-γR). Stimulation with IFN-γ for 24 h did not affect IFN-γR expression by the cells. On the other hand, IFN-γ significantly upregulated CD69 expression by the precursors afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In addition to confirming the data from Lawlor et al, who demonstrated that PBMCs stimulated with anti-CD3/CD28.2 resulted in an indirect activation of NK cells [ 48 ], our results showed that, in a preprimed immune state, MIM can considerably exacerbate the expression of this activation marker in NK and in CD8 + T cells ( Figure 4 G,H and Figure S3 ). CD69 upregulations have been shown in response to IFN-γ treatment in eosinophil precursors [ 51 ] and consecutively to a TNF-α treatment in erythroleukemic K562 cells, as it was also demonstrated that CD69 promoter contains TNF-α-responsive elements [ 52 ]. Indeed, the effect of MIM in increasing the expression of CD69 could be attributable, at least partially, to the presence of IFN-γ (6 CH) and TNF-α (5 CH) in the tested MIM capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to confirming the data from Lawlor et al, who demonstrated that PBMCs stimulated with anti-CD3/CD28.2 resulted in an indirect activation of NK cells [ 48 ], our results showed that, in a preprimed immune state, MIM can considerably exacerbate the expression of this activation marker in NK and in CD8 + T cells ( Figure 4 G,H and Figure S3 ). CD69 upregulations have been shown in response to IFN-γ treatment in eosinophil precursors [ 51 ] and consecutively to a TNF-α treatment in erythroleukemic K562 cells, as it was also demonstrated that CD69 promoter contains TNF-α-responsive elements [ 52 ]. Indeed, the effect of MIM in increasing the expression of CD69 could be attributable, at least partially, to the presence of IFN-γ (6 CH) and TNF-α (5 CH) in the tested MIM capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Overnight incubation of PBE in GM‐CSF resulted in high levels of expression of CD69 on the periphery of PBE in contrast to CD69 expression in CE that was observed throughout the cell. Although we did not examine CD69 expression by CE maintained in the absence of the cytokines used in their differentiation, Ochiai et al [22] demonstrated that at day 14 of culture, CE constitutively expressed CD69, expression of which was significantly enhanced by IFN‐γ after 24 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…It is rapidly upregulated on the membrane of lymphocytes upon stimulation, as it is observed in T cells after 1 h of treatment with PMA (Hara et al, 1986), while it reaches its maximum expression in myeloid populations in about 24 h (Yoshimura et al, 2002;Urasaki et al, 2000;Marzio et al, 1997;Ochiai et al, 2000). This time-specific regulation of CD69 expression is suggested to be in part due to distinct transcriptional regulation mechanisms, since several cis-acting elements have previously been found in CD69 locus with lineage-specific effects on transcription (Vazquez et al, 2009).…”
Section: Introductionmentioning
confidence: 86%